PENGAMBILALIHAN FLIGHT INFORMATION REGION (FIR) INDONESIA DARI SINGAPURA - Mangisi Simanjuntak (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Abstrak To date, the FIR over Batam, Tanjungpinang, and Natuna areas are still under Singapore control. The three areas in the Riau Islands Province (Kepri) were entered into the air space of block ABC. The impacts, flight activities at Hang Nadim Airport Batam and the airports included in the ABC block must wait for the notice of take-off clearance other than Air Traffic Control (ATC) Batam, also from ATC Singapore. It means that the flight was carried out on the ABC block by Indonesian aircraft, both civilian and military air planes have to be licensed from Singapore. This led to Indonesia not getting income from ATC, nor sovereign over its air. Various efforts have been made to support the government's plan to take over the management of FIR over Batam, Tanjungpinang, and Natuna of Singapore, even the takeover has been mandated in article 458 of Law No. 1 of 2009 on flights stating that the air area of the Republic of Indonesia, whose flight navigation service is delegated to other countries based on the agreement must be evaluated and served by the service provider of navigation services at the latest 15 (fifteen) years since the Act applies. Based on the law, Indonesia's foreign controlled air space must be in the control of Indonesia at the latest in 2024. Keyword: acquisition of FIR Indonesia from Singapore.